PERIPHERAL BLOOD LYMPHOCYTE SUBPOPULATIONS AND CYTOKINE PROFILE IN PERIODONTITIS - L. M. Tebloeva; O. A. Guseva; S. V. Khaidukov (Медицинская иммунология)
Functional disorders of immune system are among potential reasons of periodontal disease, thus contributing to persistence of inflammatory infiltrate in periodontal tissues and resulting into chronic local inflammation. Disturbances of local and systemic immunity play an important role in the development of periodontitis. Local immunoreactivity is associated with the induced expression of proinflammatory cytokines and attraction of pro-inflammatory cells. Systemic disorders are associated with changes in T-helper cell subpopulations, as well as those of CD3-CD8+ lymphocytes. Severity of inflammatory events and clinical course of periodontal disease is determined by qualitative and quantitative content of the T-helper cells, that express CD45RA and CD45RO antigens. Composition of T cell subsets shows direct correlations with cytokine profile in blood serum and crevicular fluid from gingival pockets. A higher IL-17 concentration, as well as increased IFNγ and IL-18 levels in blood serum of the patients suggest a potential autoimmune mechanism in periodontitis. Upon emergence and development of periodontitis, an important role may be ascribed to ‘osteocluster’ cytokines (sRANKL and OPG), and detecton of their relative contents in crevicular fluid may be proposed for testing, in order to predict clinical risks in periodontitis.